(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Abstract: This study investigates how English–Uzbek and English–Russian bilinguals conceptualize untranslatable words—lexical units that encode culturally specific meanings without direct English equivalents. Using a mixed-methods design, participants completed semantic categorization tasks and semi-structured interviews on selected Uzbek and Russian lexical items. The results show that bilinguals construct complex cognitive approximations rather than direct translations, often relying on metaphor, emotional resonance, or cultural schemas. These findings underscore the layered nature of bilingual mental lexicons and the importance of culturally grounded lexical semantics in understanding bilingual cognition.